2015
DOI: 10.1007/s10980-015-0195-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying spatiotemporal pattern of urban greenspace: new insights from high resolution data

Abstract: Context Urban greenspace provides myriad ecosystem services. To fully understand the ecological services provided by urban greenspace, it is crucial to first accurately quantify the composition and configuration, and change of urban greenspace. Objectives (1) Quantify the dynamics of greenspace in highly urbanized areas. (2) Compare and evaluate the efficacy of medium and high resolution image data on quantifying urban greenspace dynamics. Methods Using two very well-developed urban districts of Beijing, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 53 publications
(82 reference statements)
1
59
0
Order By: Relevance
“…It is one of the most important data sources for LULC monitoring at the global, national and regional scale. However, because of the limitation of spatial resolution of 30 m, relatively small but abundant changes in LULC, such as changes in urban greenspace in the inner cities, cannot be detected by TM data (Qian, Zhou, Yu, & Pickett, 2015). Imagery with higher spatial resolutions is needed to quantify such changes at very fine scales.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most important data sources for LULC monitoring at the global, national and regional scale. However, because of the limitation of spatial resolution of 30 m, relatively small but abundant changes in LULC, such as changes in urban greenspace in the inner cities, cannot be detected by TM data (Qian, Zhou, Yu, & Pickett, 2015). Imagery with higher spatial resolutions is needed to quantify such changes at very fine scales.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying such optimal patch size can have significant practical implications for urban greenspace management and design. This is because land in cities that can be used for greening is very limited (Qian et al, 2015b), and therefore knowledge on enhancing the cooling effects of greenspace by for example, optimizing their spatial configuration in addition to adding more greenspace is highly desirable. Unfortunately, we could not identify this optimal size in this study because we were not able to choose adequate number of patches of woodland with various sizes that met the experimental conditions.…”
Section: Effects Of Patch Size On Shading and Transpirationmentioning
confidence: 99%
“…Planting grass, shrubs, and trees along both sides of roads can reduce noise pollution, purify the air, beautify the streetscape, and offer inhabitants ecological, entertainment, and recreational functions [1,2]. Street greenery is a public resource that provides residents aesthetic value and ecological benefits in addition to other, unconscious benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In Los Angeles, and in Ramsey and Dakota counties in Minnesota, US, and Brisbane, Australia, some studies have also shown that street trees can increase neighbouring housing prices [29][30][31]. These studies took Earth observation approaches for extracting street tree cover data, for instance, using visual interpretation or object-oriented segmentation methods to recognize and quantify street canopy cover or other green vegetation cover in remote sensing or airborne images [2,32].…”
Section: Introductionmentioning
confidence: 99%